2011
DOI: 10.1038/leu.2010.324
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-α in acute myeloid leukemia: an old drug revisited

Abstract: Interferon-a (IFN-a), a type I IFN, is a well-known antitumoral agent. The investigation of its clinical properties in acute myeloid leukemia (AML) has been prompted by its pleiotropic antiproliferative and immune effects. So far, integration of IFN-a in the therapeutic arsenal against AML has been modest in view of the divergent results of clinical trials. Recent insights into the key pharmacokinetic determinants of the clinical efficacy of IFN along with advances in its pharmaceutical formulation, have spark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 119 publications
(146 reference statements)
5
96
0
Order By: Relevance
“…Several cytokines have been described to affect the expression of NK cell activating receptors and activity of NK cells. 39,83,84 For example IFN-a, which has already been demonstrated to exert beneficial effects in AML patients 85,86 and to be a promoter of NK cell-mediated killing, upregulates the activating NKG2D receptor [87][88][89][90] and downregulates the inhibitory NKG2A receptors. 88 NKG2D and NCR expression in AML patients was also shown to be upregulated by IL-15, 26 a currently attractive therapeutic cytokine against AML 91 with strong NK-DC crosstalk potency.…”
Section: Nk Cell Immune Escape In Aml E Lion Et Almentioning
confidence: 99%
“…Several cytokines have been described to affect the expression of NK cell activating receptors and activity of NK cells. 39,83,84 For example IFN-a, which has already been demonstrated to exert beneficial effects in AML patients 85,86 and to be a promoter of NK cell-mediated killing, upregulates the activating NKG2D receptor [87][88][89][90] and downregulates the inhibitory NKG2A receptors. 88 NKG2D and NCR expression in AML patients was also shown to be upregulated by IL-15, 26 a currently attractive therapeutic cytokine against AML 91 with strong NK-DC crosstalk potency.…”
Section: Nk Cell Immune Escape In Aml E Lion Et Almentioning
confidence: 99%
“…Although our knowledge of the role of the immune system in the control of AML is still evolving, it is well established that AML cells, like many other cancer cells, display tumor antigens that can trigger antileukemia immune responses. 1,2 In the two decades after the discovery of the first tumor-associated antigen (TAA) in melanoma, a considerable number of AML-related antigens have been characterized. This has fueled the development of antigen-directed immunotherapy approaches for AML, which can be separated into two main strategies: 'active' specific immunotherapy (that is, antigen-targeted vaccination) and 'passive' immunotherapy (that is, adoptive transfer of antigen-reactive T cells, as in the context of allogeneic HSCT or donor lymphocyte infusions (DLI)).…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that human FLT3-ITD 1 AML samples had increased miR-155 and a decreased IFN gene expression signature when compared with FLT3-WT AML, which is consistent with our mouse data. It is well established that IFN signaling has growth-inhibitory effects on the hematopoietic compartment, [20][21][22][23] and inhibition of IFN signaling was recently discovered as a novel mechanism by which FLT3-ITD 1 cells can avoid the antiproliferative effects of IFN-a and IFN-g. 24 Our results indicate that miR-155 is clearly involved in this mechanism that subverts the antiproliferative effects of IFN in this setting. Our findings are also in line with a recent study demonstrating that miR-155 promotes proliferation of CD8 1 T cells through inhibition of IFN signaling, 34 indicating that this mechanism is used by multiple cell types in vivo.…”
Section: Flt3-wt Aml (mentioning
confidence: 99%
“…Mechanistically, we show that miR-155 inhibits the response to interferon (IFN) in these model systems, and this involves direct repression of Cebpb. Interferon has previously been shown to exhibit an antiproliferative effect on early hematopoietic cells, [20][21][22][23] including in our FLT3-ITD mouse model. 24 Altogether, our study identifies a specific role for miR-155 in promoting the expansion of myeloid cells in FLT3-ITD-mediated disease in vivo, indicating that inhibition of miR-155 may be a promising new therapeutic approach for treatment of FLT3-ITD 1 AML.…”
Section: Introductionmentioning
confidence: 99%